PENGARUH ROA, NPM dan DER TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) - Yubiharto Yubiharto; Nurlaela Rakhma Hastuti (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2020)
The problem in this research is the low level of CSR disclosure or social responsibility in mining companies, even though in reality it is stated in the law that every company is required to disclose social responsibility. This research is an empirical study on mining companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The purpose of this study was to determine the effect of ROA, NPM and DER on CSR. This research is quantitative descriptive. The data used are secondary data with direct collection through the company's annual report. This sampling technique uses a separate sample criteria taken from mining companies that disclose CSR using the GRI index. Data analysis in this study used multiple linear regression analysis with SPSS 24 software. The results of this study indicate that partially the ROA variable has no significant positive effect on CSR, while the NPM and DER variables have a significant positive effect on CSR. However, all variables simultaneously influence CSR.